Direct meta substitution of calix[4]arenes - Lhoták, Pavel (Organic & biomolecular chemistry, 2022)
Calixarenes represent very popular building blocks in supramolecular chemistry. Compared to other macrocyclic families, they exhibit an almost infinite possibility of derivatization of the basic skeleton, which makes them ideal candidates for the design of new receptors or other functional systems. Although the chemistry of calixarenes is well established, there are still some substitution patterns that are unavailable or require a very lengthy synthetic approach. Among such synthetic challenges is the meta substitution of the aromatic skeleton (relative to phenolic oxygen), which, in conjunction with the 3D structure of calixarenes, leads to the inherent chirality and enables the synthesis of derivatives with a hitherto undescribed topology. This review deals with the current achievements in the meta substitution of calixarenes.
Keywords: Calixarenes; lidé; kalixareny; Oxygen; kyslík; Humans